Update on surveillance for Wilms tumor and hepatoblastoma in Beckwith-Wiedemann syndrome and other predisposition syndromes - Kalish, Jennifer M.; Becktell, Kerri D.; Bougeard, Gaëlle; Brodeur, Garrett M.; Diller, Lisa R.; Doria, Andrea S.; Hansford, Jordan R.; Klein, Steven D.; Kohlmann, Wendy K.; Kratz, Christian P.; MacFarland, Suzanne P.; Pajtler, Kristian Wilfried; et al. (Clinical cancer research, 2024)
Wilms tumors are commonly associated with predisposition syndromes, many but not all of which include overgrowth. Several of these syndromes also include a risk of other embryonal malignancies—particularly hepatoblastoma. Guidelines for surveillance in this population were published in 2017, and recently, members of the American Association for Cancer Research Pediatric Cancer Working Group met to update those guidelines with a review of more recently published evidence and risk estimates. This perspective serves to update pediatric oncologists, geneticists, radiologists, counselors, and other health care professionals on revised diagnostic criteria; review previously published surveillance guidelines; and harmonize updated surveillance recommendations in the North American and Australian contexts for patients with overgrowth syndromes and other syndromes associated with Wilms tumor predisposition.
Online verfügbar: 02. Dezember 2024
Gesehen am 30.07.2025